The Policing Strategy of Racial Profiling and its Impact on African Americans - Jones, Derrick Paul (2017)
Prior literature on racial profiling indicates that African Americans have been mistreated, harassed, and discriminated against by law enforcement because of this controversial policing strategy. The purpose of this qualitative research study was to bridge the gap in knowledge by analyzing the impact of racial profiling on African American adults and discover whether it contributed to unintentional violence in racial and ethnic minority communities. The theoretical framework for this research study was critical race theory. The research question for this study was: How does racial profiling impact African Americans' perception of the police? This phenomenological research study used purposeful sampling to locate 7 African American participants that were interviewed regarding their lived experience with racial profiling. The data collected from the interviews were organized, sorted, and coded to reveal patterns and themes. The findings revealed that the participants believed that they were discriminated against, harassed, treated like criminals, and profiled by the police because of the color of their skin without just cause. Themes that were identified from the data collected and analyzed revealed that the perceptions of the police contributed to African Americans resentment of the police, which frequently results in violence and loss of human life. The implications for positive social change for this study includes the potential redesign of policing and the criminal justice system, the development of new crime fighting strategies that do not involve racial profiling, the creation of new federal and state laws prohibiting racial profiling, cultural awareness and cultural competency education for all police officers, and improved relationships between police and the African American community